Practical On-Board Experience as a Significant Predictor of Positive Perception towards English Language Learning - Žanić Mikuličić, Jelena (Transactions on Maritime Science, 2023)
The English language is becoming increasingly important in both English-speaking and non-English-speaking countries. In the modern age, although English language skills are not the only criterion for career development, they are an indispensable tool for career advancement or obtaining a job. The aim of this study is therefore to investigate whether experience in the professional field can be considered a significant predictor of maritime students’ attitudes towards the need to learn English. For this purpose, students of undergraduate studies of Marine Engineering at the Faculty of Maritime Studies, University of Split, with no work experience (N1=65) and students of the Special Training Programme of Marine Engineering at the Faculty of Maritime Studies with at least three years practical experience (N2=38) have been asked about their attitudes towards this issue. The participants completed a newly constructed questionnaire on the need for English as a professional language. The results show a very high reliability of the questionnaire, (r ranges from 0.83 to 0.95 with p<0.01; t<0.73 with p>0.67). Furthermore, the Mann–Whitney U test has revealed a significant difference in the attitudes between the groups of participants for five out of the six variables (p<0.01). Additionally, it can be concluded that experience is a significant predictor of attitude, which implies that English language learning is a necessity in maritime practice.